2014
DOI: 10.1002/phar.1477
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor: Pharmacokinetics, Pharmacodynamics, Clinical Efficacy, and Safety

Abstract: Dual antiplatelet therapy, composed of aspirin plus a P2Y12-receptor antagonist, is the cornerstone of treatment for patients with acute coronary syndrome (ACS). A number of U.S. Food and Drug Administration–approved P2Y12-receptor antagonists are available for treating patients with ACS, including the thienopyridine compounds clopidogrel and prasugrel. Ticagrelor, the first of a new class of antiplatelet agents, is a noncompetitive, direct-acting P2Y12-receptor antagonist. Unlike the thienopyridine compounds,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
154
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(159 citation statements)
references
References 64 publications
2
154
0
3
Order By: Relevance
“…Ticagrelor, like cangrelor, is a derivative of adenosine triphosphate in which the purine was replaced by a triazolopyrimidine heterocycle [13]. This oral agent binds reversibly to the platelet P2Y 12 receptor.…”
Section: Pharmacologic Characteristics Of P2y 12 Antagonistsmentioning
confidence: 99%
“…Ticagrelor, like cangrelor, is a derivative of adenosine triphosphate in which the purine was replaced by a triazolopyrimidine heterocycle [13]. This oral agent binds reversibly to the platelet P2Y 12 receptor.…”
Section: Pharmacologic Characteristics Of P2y 12 Antagonistsmentioning
confidence: 99%
“…The active metabolite works by forming an irreversible covalent bond with receptors P2Y12. Along these covalent bonds, ADP cannot bind to receptors P2Y12 [23]. Clopidogrel has different responses that lead to inhibition of platelet aggregation be affected [24].…”
Section: Discussionmentioning
confidence: 99%
“…The great advantage is the rapid decline of antiplatelets effect after last intake. It has been reported that 24 hours after the last intake, the antiplatelet effect of ticagrelor declines by 50% [60].…”
Section: Antiplatelet Agentsmentioning
confidence: 99%